BRIDGING GENERATIONS: MORAL EDUCATION IN SCHOOLS IN FACING SOCIAL AND CULTURAL CHANGE - Husna Amin; Loso Judijanto; Ismaul Fitroh; Dina Indriyani; Hasni Noor (International Journal of Teaching and Learning, 2024)
Morality is an asset in the process of self-development. Morality has become a universal problem, both in advanced and traditional societies, because damage to morality in one person will disturb the peace of others. If there are so many morally corrupt people in society, it could be that society will be shocked. Moral education in children can change their behavior, so that when they grow up, they will become responsible adults who have respect for others and are able to face the challenges of a rapidly changing world. Increasing moral considerations in children designed through school education can improve the formation of children's personalities. By forming moral considerations, children will behave in accordance with their moral way of thinking. The three elements proposed by Durkheim to become a moral person are discipline, group attachment, and autonomy. Every individual should have these three elements to become a moral person. And moral actions are essentially the main focus in the world of morality which forms a personality that is responsible, disciplined, and becomes a good person in society, avoiding bad behavior and acting in accordance with the given moral thoughts.